EFFECTIVENESS OF USING THE SYARIAH PAYMENT GATEWAY LINKAJA SYARIAH PLATFORM IN INCREASING DIGITAL REVITALIZATION AND PROFITS OF MSMES - Walid In'am Ahmad; Achmad Fageh (Airlangga International Journal of Islamic Economics and Finance, 2025)
This study aims to analyze the benefits of using a Sharia payment gateway in encouraging digitalization, especially for MSMEs, through the LinkAja Syariah application. The method used is a qualitative approach based on literature studies from various journals and relevant articles. The results of the study show that the adoption of the Sharia digital payment system has increased significantly, reflected in the growth of LinkAja Syariah users by 1.6 million from 2020 to 2024, with a total reaching 10 million users. This digitalization supports time efficiency, and more accurate financial records, and facilitates QRIS payments, Sharia bank transfers, and ziswaf payments. Even without primary data, the increase in indicators such as cash deposit and withdrawal transactions (53–65%) and the increase in LinkAja Syariah revenue by 23% in 2023 show the potential for increasing MSME profitability through the use of this technology.